Analysis of basic technical skills in underhand volleyball passing for extracurricular students - Pekei, Selpina; Harmaman, Harmaman; Bumburo , Bandung; Putro , Waskito Aji Suryo; Sahidi, Sahidi (Jurnal Ilmu Keolahragaan, 2026)
Background Volleyball is a sport taught in elementary schools and requires good basic techniques, one of which is the underhand pass. Mastering the underhand pass is crucial for success, so it is important to understand students’ proficiency in this technique, especially in extracurricular activities. Objectives This study aims to determine the basic technical ability in underhand passing in volleyball among elementary school students. Methods This study is a quantitative study using descriptive analysis. The population in this study consisted of all sixth-grade students at Muhammadiyah Aimas Elementary School for the 2025/2026 academic year, totaling 41 students. The sampling technique used was total sampling, meaning the entire population was sampled. The research instrument consisted of a test of basic underhand passing skills, while data analysis employed quantitative descriptive techniques. Results The results of the study show that of the 41 students who took the test, 15 students (37%) scored in the “very good” category (scores 10–12), 17 students (42%) were in the “fair/not very good” category (scores 8–9), 7 students (17%) were in the “poor” category (scores of 6–7), and 2 students (5%) were in the “very poor” category (scores of 4–5). Conclusion Based on the research results, it can be concluded that the basic underhand passing skills of extracurricular students at SD Muhammadiyah Aimas, Sorong Regency, generally fall into the “good” category. Therefore, more structured training is needed to improve their underhand passing skills.